2020
DOI: 10.7454/uiphm.v4i1.260
|View full text |Cite
|
Sign up to set email alerts
|

Classical Music Therapy as The Intervention to Relieve Headache in A Meningitis Patient

Abstract: <div><p class="Keywords"><strong>Objective</strong>: Headache is a manifestation of inflammatory response from meningeal infection. Headache may affect client physically and psychologically thus it requires treatment. This paper aimed to analyze implementation of classical music therapy as non-pharmacological intervention in relieving headache in patient with meningitis.</p><p class="Keywords"><strong>Methods</strong>: This was a case study to evaluate the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…11 In a more specific approach, it is revealed that classical music can be used in the context of headaches resulting from meningitis, which, despite not being the focus of this work, has similar effects on the brain region of the patient. 9 Thus, a patient was exposed to classical music for 12 minutes and 15 seconds for 3 sessions over 3 days, obtaining positive results, relieving the intensity of pain, and reducing emotional stress. In the same way, when analyzing what was raised by Study 4 (Table 1), referring to the effects of classical music therapy against headache in hypertensive patients, it was shown to be advantageous, since all the groups that received the intervention had the intensity of the symptom reduced.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In a more specific approach, it is revealed that classical music can be used in the context of headaches resulting from meningitis, which, despite not being the focus of this work, has similar effects on the brain region of the patient. 9 Thus, a patient was exposed to classical music for 12 minutes and 15 seconds for 3 sessions over 3 days, obtaining positive results, relieving the intensity of pain, and reducing emotional stress. In the same way, when analyzing what was raised by Study 4 (Table 1), referring to the effects of classical music therapy against headache in hypertensive patients, it was shown to be advantageous, since all the groups that received the intervention had the intensity of the symptom reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Again, it is important to emphasize that the tests of the referred studies were not directed to patients with tension-type headache, thus becoming a factor for analogies, aiming at the physiological effect that music caused in both studies, dilating the encephalic vessels, and making the blood more fluid in this region. 9,11,12…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation